Alteration in the Expression of Genes Involved in Cerebral Glucose Metabolism as a Process of Adaptation to Stressful Conditions - Mariola Herbet; Iwona Piątkowska-Chmiel; Monika Motylska; Monika Gawrońska-Grzywacz; Barbara Nieradko-Iwanicka; Jarosław Dudka (Brain Sciences, 2022)
Exposure to chronic stress leads to disturbances in glucose metabolism in the brain, and changes in the functioning of neurons coexisting with the development of depression. The detailed molecular mechanism and cerebral gluconeogenesis during depression are not conclusively established. The aim of the research was to assess the expression of selected genes involved in cerebral glucose metabolism of mice in the validated animal paradigm of chronic stress. To confirm the induction of depression-like disorders, we performed three behavioral tests: sucrose preference test (SPT), forced swim test (FST), and tail suspension test (TST). In order to study the cerebral glucose metabolism of the brain, mRNA levels of the following genes were determined in the prefrontal cortex of mice: Slc2a3, Gapdh, Ldha, Ldhb, and Pkfb3. It has been shown that exogenous, chronic administration of corticosterone developed a model of depression in behavioral tests. There were statistically significant changes in the mRNA level of the Slc2a3, Ldha, Gapdh, and Ldhb genes. The obtained results suggest changes in cerebral glucose metabolism as a process of adaptation to stressful conditions, and may provide the basis for introducing new therapeutic strategies for chronic stress-related depression.